Application of a Cost-Allocation Model to Swiss Bus and Train Lines. Issue 8 (December 2018) - Sinner, Marc; Weidmann, Ulrich; Nash, Andrew
Public transport costs are an important decision factor when making system design choices and network or timetable planning. Although many cost models of varying degrees of sophistication have been proposed in literature, practitioners often use relatively simple models such as purely vehicle-kilometer-based cost estimations. This paper applies a cost-allocation model to Swiss bus and train lines. The proposed model is based on operating statistics including 'productive hours', vehicle-kilometers, vehicle number and size. The cost model is then applied to a case study for a generic public transport line with a typical demand distribution. The case study calculates the demand level at which train service becomes more effective than bus service for various combinations of minimal frequency, average speed and maximum number of coupled Electric Multiple Units.